Analysis of Type Selection Scheme for Axle Box Bearing of 250 km/h Standard EMUs - Yunlong ZHANG; Bin JIANG; Hongjiang XU; Hanchen ZHANG; Xiuyan LI (机车电传动)
According to the structural dimensions, lubrication, sealing, life, reliability and maintainability of axle box bearings,the performances of bearings used in existing EMUs were analyzed in detail. Combining with the characteristics of 250 km/h standard EMUs and the future development direction, the feasible suggestions for the selection of bearings were provided, and selection scheme of axle box bearing for 250 km/h standard EMUs was formed.